The Prevalence of Hepatitis A in Iranian Children and Adolescents - E Mousavi; AA Khaleghi; M Mohammadi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Hepatitis A is considered a disease with high prevalence in developing countries, and the spread of this disease in children is considered an important alarm for societies. The aim of this systematic review and meta-analysis is to investigate the prevalence of hepatitis A in Iranian children and adolescents. Methods: In this systematic review and meta-analysis, a systematic search was performed on PubMed, ScienceDirect, SID and Google Scholar databases using the keywords “Iranian children and adolescents” and “hepatitis A infection” in the time frame of 2000-2022. In this study, the age range of 1 to 19 years, which includes the prevalence reported in children and adolescents, was investigated. Findings: In 39 studies with a sample size of 11,795 children and adolescents aged 1 to 19 years based on meta-analysis, the prevalence of hepatitis A in Iranian children and adolescents was reported as 37.3% (95% CI: 29.6-45.7). Based on subgroup analysis by age, in a total of 24 studies with a sample size of 6739 adolescents, the prevalence of hepatitis A in Iranian adolescents was 54.8% (95% CI: 47-62.4). In a total of 9 studies with a sample size of 2055 children, the prevalence of hepatitis A in Iranian children was reported as 14.6% (95% CI: 8.8-23.4). Conclusion: The results of this study showed that the prevalence of hepatitis A is relatively high in Iranian children and adolescents, and accordingly, it requires the attention of health policy makers.